Faktor yang Berhubungan dengan Kinerja Perawat di Instalasi Rawat Inap Rumah Sakit Umum Daerah Batara Siang Kabupaten Pangkep - Hartati Hartati; Noer Bahry Noor; Adelia U.Ady Mangilep (Hasanuddin Journal of Public Health, 2020)
Nurse performance is not only a global issue in Batara Siang District Hospital, Pangkep Regency but shows data on patient satisfaction that changes in 2016 that is 95%, in 2017 which is 96.38%, in 2018 which is 96% and in 2019 amounting to 76.79%. Where patient satisfaction Batara Siang Hospital Pangkep Regency in 2019 did not meet the minimum hospital service standards in 2012 that is equal to 85%. To study the relationship between motivation, ability, leadership, attitude, workload, knowledge, and rewards with the performance of nurses in RSUD Batara Siang, Pangkep Regency. This research is a quantitative study with a cross sectional study approach. This research was conducted in December 2019. The sampling method was 165 people. Data collection tool using a questionnaire. Data analysis used univariate, bivariate analysis and data presentation in the form of tables accompanied by narration. The performance of nurses in Batara Siang District Hospital in Pangkep This research shows the relationship between leadership dimensions and workload on nurse performance with the Likelihood Ratio test found that the value of p <0.05. This study has to do with the dimensions of leadership and workload on nurse performance.